Development of Pop-Up Flashcard Media by Strengthening the Curious Character of Class IV Elementary School Students - Nabila, Putri Assyaffa; Utama, Candra; Untari, Esti (Proceedings Series of Educational Studies, 2024)
This research was conducted because there is a need for learning media to support students memory on the material of flower body parts and their functions. Based on this needs analysis, researchers developed science and technology learning media in elementary schools. The aim of this development research is to create pop-up flashcard media in science subjects that is valid according to validators, practical according to teachers and students, and effectively applied in learning, as well as influencing the curious character of students. Research and Development (R&D) and ADDIE are the types and models of research used. The subjects of this research were 9 class IV students at SDN Polehan 05 and 18 class IVA students at SDN Madyopuro 04 Malang. Based on research results, the pop-up flashcard media was declared valid, practical, effective, and had an effect on students curiosity. Keywords: learning media; pop-up flashcard; curiosity characters